Bimbingan Nilai-Nilai Spiritual Di Madrasah Aliyah Mafaza Bantul Yogyakarta - Heri Fadli Wahyudi (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
The cultivation of spiritual values to learners is a very vital step in shaping the characteristics and character of the human person, because the internalization of spiritual values is closely related to the cultivation of religious values, and is part of the formation of adolescent character as the next generation of religion and nation. This research is to find out the process of planting and internalizing spiritual value education conducted at The Senior high school of Mafaza Institute located in the Maguntapan Bantul area of Yogyakarta, while the type in this study is qualitative with a descriptive approach, while the subject in this study is teachers or teachers at this institution as well as some M.A. Mafaza students. While the data collected passes through the process of interviews, observations and documentation which then the author of the data analysis to draw conclusions. The results of this study show the following: 1). The process of planting and internalizing values and spiritual in this institution is carried out with an understanding of the material in the classes. 2). Then as a follow-up in the form of application in programs and activities such as requiring mandatory congregational prayers, sunnah worship and others, there are also activities such as the loving mosque and the the Adiwiata program. So from there it is seen that all aspects in value and spiritual, namely the aspect of Aqidah and Worship become the center of attention in planting to their students. So that it covers everything, either in the pattern of vertical relationship (Servant-Godnya) or horizontal (Servants and Environment).